Event, iterability, and justice practiced in the sense of law: a derridean reading of Arthur Miller’s The Crucible - Hooti, Noorbakhsh; Ghaderi, Ali (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2015)
This paper aims to investigate Arthur Miller’s The Crucible in terms of Derridean critical terms, particularly event, iterability, and justice. Furthermore, through this close reading, the text is scrutinised considering concepts of undecidability, identity, and alterity. Most assuredly, core to body of this Miller’s masterpiece is the Salem witch trials. Firstly, it is demonstrated how this play’s account of witch trials could be considered an event, in Derridean terms, and how the concept of iterability would function within the text. This will result in re-echoing of the same event through many epochs in a variety of voices. Secondly, this paper scrutinises the text to identify how human constructed institutions avoid what Derrida calls play of structure by assuming centres and logos in themselves and presuming whatever tries to question them as the other. This is depicted by Miller through juxtaposing religion and magic and showing how they react towards each other throughout the play. Inevitably, the discussion of identity and alterity (a term under the influence of Derrida) is to follow next to show how identity (as the culture that shapes it) is different from itself and, ergo, has no pure origin of its own. Lastly, this study examines the practice of law specifically in the court scene of the play to show how justice and law are perceived and to conclude that the role of undecidability is crucial to the process of decision taking in the court if any degree of justice should very like to be possible.